India's reforms : how they produced inclusive growth - Bhagwati, Jagdish N., 1934-; Panagariya, Arvind (Oxford : Oxford University Press, 2012)
Openness has affected neither poverty nor inequality adversely. When surveyed, people in disproportionately large volumes from all groups say that their fortunes are improving. The essays in this volume show that trade oppenness has helped reduce poverty among most social groups.
Includes index.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Keywords: Poverty -- India; Equality -- India; India -- Commercial policy; India -- Economic conditions; India -- Social conditions; India -- Politics and government